APAKAH PROGRAM “JAMULA” BERDAMPAK TERHADAP PERUBAHAN SOSIAL EKONOMI MASYARAKAT KABUPATEN LAMONGAN? DITINJAU DARI TEORI MERILEE GRINDLE - Royali, Ahmad Sayuti; Ardhana, Vicky; Awalia, Mellysa Nur; Sholiha, Farra Ummush (ANALISIS, 2024)
The purpose of this study is to analyze the influence of policy content and implementation context in the Merilee Grindle theory of the Jamula policy on the Sukodadi-Sumberwudi highway of Pucangro Village on the impact and changes and acceptance of the people of Lamongan district. This research was conducted quantitatively with an exploratory approach. The sample of this study amounted to 100 people from the people of Lamongan Regency and the sample was obtained from a nonprobability sampling technique with snowball sampling. The data obtained is then processed using the Structural Equation Model analysis tool based on Partial Least Square (SEM-PLS). The hypothesis of this study is that the policy content variable and the implementation context variable of the Jamula policy on the Sukodadi-Sumberwudi highway of Pucangro Village have an influence on impact variables as well as change and acceptance variables. The test results show that policy content has an influence on impact, policy content has an influence on change and acceptance, and the context of implementation has an influence on change and acceptance. There is one hypothesis that is not empirically proven, namely that the context of implementation has no effect on impact. The conclusions of this study are: (1) the three hypotheses based on the theory of the merilee grindle implementation model are acceptable or empirically provable; (2) one hypothesis is rejected is the influence of the implementation context on the impact and the author assumes that the implementation context carried out by the Lamongan Regency government is ineffective, so that the community does not feel the positive impact of the Jamula policy on the Sukodadi-Sumberwudi highway in Pucangro Village. The Jamula program provides positive benefits to the community, so the government must be responsive and timely in repairing roads to increase community satisfaction.